Measuring the perception of violence against women at UABC Law School, Campus Valle Dorado - Soberano Serrano, Alma Alejandra; Delhumeau Rivera, Sheila (Cuestiones de Género: de la igualdad y la diferencia, 2019)
Despite of the efforts made by civil society and the legal modifications made in the Mexican legislation, the existing violence towards women does not decrease and it shows its normalization in professions like Law that require alternatives based on gender sensitization. This work consists of the results of a survey on perception of violence against women with students of the Law School of the Autonomous University of Baja California in the summer of 2018, which through six dimensions (physical violence, psychological violence, sexual violence, deprivation, normalization of violence and social capital) tries to understand the factors considered as violent, while presenting a proposal for protocol of attention to this problem in the university campus.